EFEK POSTUR TUBUH TERHADAP KESEIMBANGAN LANJUT USIA DI DESA SUKA RAYA KECAMATAN PANCUR BATU - Sulaiman ST., M.K.M; Anggriani Anggriani (Prodi Kesehatan Masyarakat FKM UIN Sumatera Utara Medan, 2018)
The most important think of every people (Children until Elderly) is body posture. In other hand the excessive burden of elderly posture is always associated with the high risk of falls. So that, the balancing of elderly posture is important to owned by the elderly person. This study aims to find out the effect of body posture on the elderly balance in Suka Raya Village. This study used a cross-sectional approach with all of elderly person in Sukaraya Village as the population. To collect the data used Non-Probability-Sampling, in this case take thirty elderly persons. The result of this study showed that twenty elderly persons with kyphosis find fifteen of them has open-eye static balance and seventeen of them has closed-eye static balance with a bad category. Whereas as many as ten people who have not kyphosis found two of them with open-eye static balance and closed-eye with bad category. The risk of kyphosison the elderly static-balance with bad category of open-eye and closed eye static balance is twelve times larger more with open-eye static, and twenty-two point six times larger with closed-eyes on normal posture. Conclusion, there is correlation between the effects of body posture on the elderly static-balance, and kyphosis of the elderly person more have not static-balance. The elderly persons need to caring their health in order to keep the balancing of body. Keyword: Posture, Kyphosis, Balancing, Elderly